1992
DOI: 10.4028/www.scientific.net/msf.94-96.563
|View full text |Cite
|
Sign up to set email alerts
|

Grain Growth in Al-2% Cu Thin Films

Abstract: DISCLAIMERThis document was prepared as an account of work sponsored by the United States Government. Neither the United States Government nor any agency thereof, nor The Regents of the University of California, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any ir_ormation, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Another recent revelation is that the declining metallicity gradient of both stars and gas appears to flatten out beyond several disk scalelengths (q.v. Vlajic 2010; Sanchez et al 2014). It is interesting to consider whether some of the extended H I envelopes identified in nearby groups (e.g., Leo, Cen, M81, M83) normally attributed to tidal debris from high column regions is in fact compressed material from proto-disk regions.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent revelation is that the declining metallicity gradient of both stars and gas appears to flatten out beyond several disk scalelengths (q.v. Vlajic 2010; Sanchez et al 2014). It is interesting to consider whether some of the extended H I envelopes identified in nearby groups (e.g., Leo, Cen, M81, M83) normally attributed to tidal debris from high column regions is in fact compressed material from proto-disk regions.…”
Section: Discussionmentioning
confidence: 99%
“…[1,22,23] At the same time, copper segregates at the grain boundaries and dislocations. [24] The phase sequence and microstructure of Al(Cu) have been studied extensively.…”
Section: A Grain Size and Microstructurementioning
confidence: 98%
“…Grain growth in Al(Cu) begins around 200°C [1,22,23] and progresses with increasing temperature. [1,22,23] At the same time, copper segregates at the grain boundaries and dislocations.…”
Section: A Grain Size and Microstructurementioning
confidence: 99%
“…The radial distribution of gas-phase oxygen abundances traced by H ii regions has been investigated in the disks of many spiral galaxies (Vila-Costas & Edmunds 1992;Zaritsky et al 1994;van Zee et al 1998;Pilyugin et al 2004;Moustakas et al 2010;Gusev et al 2012;Pilyugin et al 2014a;Sánchez et al 2014). It was found that almost all spiral galaxies show radial abundance gradients in the sense that their inner H ii regions (i.e., those closer to the galactic centers) have higher oxygen abundances than the outer ones.…”
Section: Introductionmentioning
confidence: 99%